NmFGF1-Regulated Glucolipid Metabolism and Angiogenesis Improves Functional Recovery in a Mouse Model of Diabetic Stroke and Acts via the AMPK Signaling Pathway - Zhao, Yeli; Ye, Shasha; Lin, Jingjing; Liang, Fei; Chen, Jun; Hu, Jian; Chen, Kun; Fang, Yani; Chen, Xiongjian; Xiong, Ye; Lin, Li; Tan, Xianxi (Frontiers in Pharmacology, 2021)
Diabetes increases the risk of stroke, exacerbates neurological deficits, and increases mortality. Non-mitogenic fibroblast growth factor 1 (nmFGF1) is a powerful neuroprotective factor that is also regarded as a metabolic regulator. The present study aimed to investigate the effect of nmFGF1 on the improvement of functional recovery in a mouse model of type 2 diabetic (T2D) stroke. We established a mouse model of T2D stroke by photothrombosis in mice that were fed a high-fat diet and injected with streptozotocin (STZ). We found that nmFGF1 reduced the size of the infarct and attenuated neurobehavioral deficits in our mouse model of T2D stroke. Angiogenesis plays an important role in neuronal survival and functional recovery post-stroke. NmFGF1 promoted angiogenesis in the mouse model of T2D stroke. Furthermore, nmFGF1 reversed the reduction of tube formation and migration in human brain microvascular endothelial cells (HBMECs) cultured in high glucose conditions and treated with oxygen glucose deprivation/re-oxygenation (OGD). Amp-activated protein kinase (AMPK) plays a critical role in the regulation of angiogenesis. Interestingly, we found that nmFGF1 increased the protein expression of phosphorylated AMPK (p-AMPK) both in vivo and in vitro. We found that nmFGF1 promoted tube formation and migration and that this effect was further enhanced by an AMPK agonist (A-769662). In contrast, these processes were inhibited by the application of an AMPK inhibitor (compound C) or siRNA targeting AMPK. Furthermore, nmFGF1 ameliorated neuronal loss in diabetic stroke mice via AMPK-mediated angiogenesis. In addition, nmFGF1 ameliorated glucose and lipid metabolic disorders in our mouse model of T2D stroke without causing significant changes in body weight. These results revealed that nmFGF1-regulated glucolipid metabolism and angiogenesis play a key role in the improvement of functional recovery in a mouse model of T2D stroke and that these effects are mediated by the AMPK signaling pathway.